Extraction and exchange behavior of metal species in therapeutically applied peat - Rosa, André Henrique [UNESP]; Rocha, J. C.; Burba, P. (Elsevier B.V., 2002)
The binding and availability of metals (Al, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Ni, Pb, Zn) in therapeutically applied peat (GroBes Gifhorner Moor, Sassenburg/North Germany) was characterized by means of a versatile extraction approach. Aqueous extracts of peat were obtained by a standardized batch equilibrium procedure using high-purity water (pH 4.5 and 5.0), 0.01 mol l(-1) calcium chloride solution, 0.0 1 mol l(-1) ethylenediaminetetraacetic acid (EDTA) and 0.01 mol l(-1) diethylenetriarnine pentaacetic acid (DTPA) solution as metal extractants. In addition, the availability of peat-bound metal species was kinetically studied by collecting aliquots of extracts after different periods of extraction time (5, 10, 15, 30, 60 and 120 min). Metal determinations were performed by atomic spectrometry methods (AAS, ICP-OES) and dissolved organic matter (DOM) was characterized by UV/Vis measurements at 254 and 436 nm, respectively. of the extractants studied Ca, Mg and Mn were the most available metals, in contrast to peat-bound Fe and Al. The relative standard deviation s(r) of the developed extraction procedures was mostly in the range of 4 to 20%, depending on the metal and its concentration in peat. A pH increase favored the extraction of metals and DOM from peat revealing complex extraction kinetics. Moreover, a competitive exchange between peat-bound metal species and added Cu(II) ions showed that > 100 mg of Cu(II) per 50 g wet peat was necessary to exchange the maximum of bound metals (e.g. 21.8% of Al, 3.9% of Fe, 79.0% of Mn, 81.9% of Sr, related to their total content). (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: metal availability; metal extractants; extraction kinetics; dissolved organic matter